Positive Aspects of Social Media in Various Fields - Nagalakshmi, S (International Journal of Computer Sciences and Engineering, 2025)
Now a days, social media plays an important role in our life we are using it to keep in touch with our friends and relatives. These tools are very useful when we talk about business too. In this paper we cover all aspects of social media with its positive effect. Social media is an integral part of today’s society. Social media changes the way people interact with each other by offering more convenience but less quality. On the positive side, Social networks can act as individual tools for professionals to market their skills and seek business opportunities. Here we cover every aspect of social media with its positive effects. Some of the sites have become a day to day routine for the people. Social media has been mainly defined to refer to “the many relatively inexpensive and widely accessible electronic tools that facilitate anyone to publish and access information, collaborate on a common effort, or build relationship”. Focus is on the particular field like education, Healthcare, business, aerospace, youth, chemical engineering and society.